Factors associated with decreased bone mineral density in postmenopausal women with schizophrenia - Liang Y (Dove Medical Press, 2016)
Ying Liang,1 Jian Huang,1 Jing-bin Tian,2 Yuan-yuan Cao,2 Guo-ling Zhang,2 Chun-gang Wang,2 Ying Cao,2 Jian-rong Li2 1National Clinical Research Center for Mental Disorders, Peking University Sixth Hospital, Institute of Mental Health, and the Key Laboratory of Mental Health, Ministry of Health, Peking University, Beijing, People’s Republic of China; 2Psychiatry Department, Changping District Hospital of Integrated Chinese and Western Medicine, Beijing, People’s Republic of China Objective: This study examined the risk factors for decreased bone mineral density (BMD) in postmenopausal women with schizophrenia. Methods: Cluster sampling method was adopted in this large-sample, cross-sectional study. A total of 219 postmenopausal female inpatients with schizophrenia were selected and interviewed in Beijing. The average age of the patients was 60.4±7.0 years. Clinical assessment instruments included the Positive and Negative Syndrome Scale (PANSS) and a questionnaire with detailed general information and disease-related investigations. Laboratory measurements included prolactin (PRL), estradiol, progesterone, thyroid stimulating hormone, FT3, and FT4. BMD testing was performed by dual-energy X-ray absorptiometry. Results: The prevalence of osteoporosis or osteopenia was 66.2% (n=145). Decreased BMD was associated with age, illness duration, therapeutic dose (equivalent chlorpromazine dose), treatment duration, PANSS-negative scores, body mass index (BMI), daily exercises (min/d), drinking (unit/wk), PRL, and estradiol. Multiple logistic regression analysis revealed that age, treatment duration, PANSS-negative score, BMI, and PRL were significantly associated with decreased BMD. Conclusion: Prevalence of BMD loss was higher in Chinese postmenopausal women with schizophrenia compared to the normal BMD group. A combination of demographic and clinical factors play important roles in determining decreased BMD, including older age, longer treatment duration, more PANSS-negative scores, higher BMI, and higher PRL level. Keywords: schizophrenia, bone density, risk factors